Selforganization in Complex Systems: The Past, Present, and Future of Synergetics Proceedings of the International Symposium, Hanse Institute of Advanced Studies, Delmenhorst, Germany, November 13-16, 2012 - Wunner, Günter; Pelster, Axel (Understanding Complex Systems, 2016)
This proceedings volume contains talks and poster presentations from the International Symposium "Self-Organization in Complex Systems: The Past, Present, and Future of Synergetics", which took place at Hanse-Wissenschaftskolleg, an Institute of Advanced Studies, in Delmenhorst, Germany, during the period November 13 - 16, 2012. The Symposium was organized in honour of Hermann Haken, who celebrated his 85th birthday in 2012. With his fundamental theory of Synergetics he had laid the mathematical-physical basis for describing and analyzing self-organization processes in a diversity of fields of research. The quest for common and universal principles of self-organization in complex systems was clearly covered by the wide range of interdisciplinary topics reported during the Symposium. These extended from complexity in classical systems and quantum systems over self-organisation in neuroscience even to the physics of finance. Moreover, by combining a historical view with a present statusreport the Symposium conveyed an impression of the allure and potency of this branch of research as well as its applicability in the future.